Green Finance and Sustainable Development: Paths and Policies for Global Economic Transformation - Zhu, Ming (International Journal of Global Economics and Management, 2024)
This article provides an in-depth exploration of the key role of green finance in the transformation of the global economy. First, the definition and basic principles of green finance are clarified, and its practice and development, as well as its close relationship with sustainable development, are analyzed in detail. In terms of environment, green finance contributes to environmental protection by mitigating climate change and promoting the development of clean energy. At the social level, it promotes social justice and inclusive growth and improves social well-being. In terms of economy, green finance promotes innovation and industrial upgrading, and improves the resilience and sustainability of the economy. However, green finance faces challenges such as information asymmetry and policy instability. In its future development directions and suggestions, it calls for efforts such as international cooperation, policy support, professional training, business guidance, and public education to promote a more healthy, transparent, and sustainable development of the green financial market. The article concludes by emphasizing that green finance is a key force leading the transformation of the global economy. It not only plays a role in the environmental field, but also plays a vital role in promoting the green transformation of enterprises and promoting the upgrading of economic structure.